1998
DOI: 10.1210/endo.139.12.6385
|View full text |Cite
|
Sign up to set email alerts
|

Troglitazone Inhibits Progesterone Production in Porcine Granulosa Cells**This work was supported by a grant from the Sankyo Corporation (to R.J.U. and A.G.) and NIH Grant RO1-CA45181 (to M.N.).

Abstract: Troglitazone (a thiazolidinedione that improves insulin resistance) lowers elevated androgen concentrations in women with polycystic ovarian syndrome. In this study, we assessed the direct effects of troglitazone on steroidogenesis in porcine granulosa cells. Troglitazone inhibited progesterone production in a dose- and time-dependent manner (earliest effects at 4 h, maximum at 24 h) without affecting cell viability. Progesterone production was also inhibited by troglitazone in the presence of 25-hydroxycholes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The activation of PPAR␥ has been shown to affect progesterone production. PPAR␥ ligands inhibited progesterone production in cultured human and porcine granulosa cells (43); however, they stimulated the secretion of both progesterone and E2 in cultured rat granulosa cells (31). In our in vivo study, progesterone levels were reduced in virgin mice upon inactivation of the PPAR␥ gene in granulosa cells and the corpora lutea.…”
Section: Ppar␥ Ablation From the Epithelial Compartment Did Not Inducmentioning
confidence: 48%
“…The activation of PPAR␥ has been shown to affect progesterone production. PPAR␥ ligands inhibited progesterone production in cultured human and porcine granulosa cells (43); however, they stimulated the secretion of both progesterone and E2 in cultured rat granulosa cells (31). In our in vivo study, progesterone levels were reduced in virgin mice upon inactivation of the PPAR␥ gene in granulosa cells and the corpora lutea.…”
Section: Ppar␥ Ablation From the Epithelial Compartment Did Not Inducmentioning
confidence: 48%
“…In turn, a lack of changes in P 4 or E 2 production was observed in human granulosa-lutein cells [29]. There are also studies showing an inhibitory effect of PPARg activators on P 4 production by cultured porcine and human LH-stimulated granulosa cells [37,38]. Recent data showed that the activation of PPARa and PPARg affected steroidogenesis and follicle development in mouse preantral follicles treated with tumor necrosis factor alpha (TNFa), used as a model for studying follicle development in patients with PCOS [39].…”
Section: Ppars and Steroidogenesismentioning
confidence: 99%
“…For instance, a stimulatory effect of PPARg activation on steroidogenesis can be mediated by up-regulation of steroidogenic acute regulatory (StAR) protein in human and macaque granulosa cells [44,45] or by 3b-HSD in porcine ovarian follicles [36]. An opposite effect of PPARg ligands on 3b-HSD expression and P 4 release was observed in porcine granulosa cells [37]. There are also studies showing that PPARg or PPARa activation inhibited aromatase expression in human granulosa cells and mouse ovary [46,47].…”
Section: Ppars and Steroidogenesismentioning
confidence: 99%
“…PPAR deletion has no apparent effect on the fertility of mice, but the deletion of PPAR and PPAR / does have this effect (Lee et al 1995, Peters et al 2000, Barak et al 2002. In the ovaries of rodents and ruminants, PPAR is expressed strongly in the granulosa cells, and less strongly in the theca cells and corpus luteum (Gasic et al 1998, Komar et al 2001, Froment et al 2003. PPAR is detected early in folliculogenesis, at the primary/secondary follicle stage (Komar 2005).…”
Section: Testismentioning
confidence: 99%
“…Thus, TZDs stimulate in vitro the secretion of steroids (progesterone and estradiol) by rat and ovine granulosa cells (Komar et al 2001, Froment et al 2003, bovine lutein cells (theca-and granulosa-derived cells) (Lohrke et al 1998) and porcine theca cells (Schoppee et al 2002), whereas they inhibit the secretion of progesterone and estradiol by porcine granulosa cells and by human granulosa cells from patients who underwent in vitro fertilization (Gasic et al 1998, Mu et al 2000. The species and the status of the granulosa cell differentiation (follicular phase, before or after the gonadotropin surge) could modulate these actions of TZDs on steroidogenesis.…”
Section: Expression and Localization (mentioning
confidence: 99%